Properties of capsaicinoids for the control of fungi and oomycetes pathogenic to pepper. (1st March 2013) - Veloso, J.; Prego, C.; Varela, M. M.; Carballeira, R.; Bernal, A.; Merino, F.; Díaz, J.; Papen, H.
Abstract Capsaicinoids are pungent compounds found in pepper (Capsicum spp.) fruits. Capsaicin showed antimicrobial activity in plate assays against seven isolates of five species of fungi and nine isolates of two species of oomycetes. The general trend was that oomycetes were more inhibited than fungi. Assays of capsaicin biosynthetic precursors suggest that the lateral chain of capsaicinoids has more inhibitory activity than the phenolic part. In planta tests of capsaicinoids (capsaicin and N‐vanillylnonanamide) applied to the roots demonstrated that these compounds conferred protection against the pathogenic fungus Verticillium dahliae and induced both chitinase activity and expression of several defence‐related genes, such as CASC1, CACHI2 and CABGLU. N‐Vanillylnonanamide infiltrated into cotyledons confers systemic protection to the upper leaves of pepper against the fungal pathogen Botrytis cinerea. In wild‐type tomato plants such cotyledon infiltration has no protective effect, but is effective in the Never‐ripe tomato mutant impaired in ethylene response. A similar effect was observed in tomato after salicylic acid infiltration.